Pricing Strategy for Pharmaceutical Products to Improve Profitability: A Case Study of Eliezer Sejahtera Main Clinic Pharmacy, Nabire - Evelyn Angela Sibarani; Sita Yubelina Sabandar; Manuel August Todingbua (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
Pricing of pharmaceutical products is a strategic component in pharmacy management that directly influences a clinic’s profitability. This study aims to analyze the pricing process and evaluate the impact of pricing strategies on profit improvement at the Pharmacy Installation of Klinik Utama Eliezer Sejahtera Nabire. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and internal document analysis. The findings reveal that the clinic applies a cost-plus pricing strategy, which calculates selling prices based on purchase cost, operational expenses, and a predefined profit margin, while adhering to government regulations such as the Highest Retail Price (HET). This strategy has contributed to financial stability and patient loyalty; however, challenges such as fluctuating distributor prices and low consumer purchasing power hinder optimal profit realization. Strategic recommendations include regular price evaluations, implementation of digital inventory and pricing systems, and the development of flexible pricing schemes tailored to patient segments. The study offers practical insights for pharmacy service managers and serves as a reference for developing adaptive and sustainable pricing policies in clinical settings.